وسائل التعليم اللغة العربية وتطوره في مهارة القراءة بكلية التربية الجامعة التهذيب الإسلامية: وسائل التعليم اللغة العربية وتطوره في مهارة القراءة بكلية التربية الجامعة التهذيب الإسلامية - Abidin, Hasan (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2020)
Study of Arabic regarded as a difficult subject matter by the students of Arabic Departement of STAI At-Tahdzib Ngoro Jombang. The difficulty is due to a lot of various factors, one of them is the using of Arabic books published be Middle East schools. The title of the research: Teaching Balaghah on Arabic Language Education Program of STAI At-Tahdzib Ngoro Jombang. in Improving Student Achievement (A Feasibility Analysis)”. This research is aimed at understanding and analyzing: (a) The Arabic subject on Arabic Departement of STAI At-Tahdzib Ngoro Jombang; (b). The learning achievement of Arabic Subject of students of Arabic Departement of STAI At-Tahdzib Ngoro Jombang.; (c). The effect Instructional Materials Arabic feasibility study on student achievement of Arabic Departement of STAI At-Tahdzib Ngoro Jombang. Before distributing the data, validity and reliability tests were carried out; the data obtained were processed with the computer program SPSS (Statistical Program for Social Science) version 16.0 with a 95 % significance level (α= 5 %). As for testing the researchers' hypothesis using Simple Linear Regression Test. The results showed: (a). Arabic Subject of the Arabic Departement of STAI At-Tahdzib Ngoro Jombang. was feasible for use. This was indicated by a score of an average value of 47.2; (b). Student Achievement of Arabic of Arabic Departement of STAI At-Tahdzib Ngoro Jombang. was average height with an average score of 43.5, and (c). There was a significant relationship between Instructional Materials Arabic Feasibility study on student achievement of Arabic Departement of STAI At-Tahdzib Ngoro Jombang. It was shown in the results of the correlation between variables X and Y, the value obtained was 0.892 means a significant difference between the feasibility Arabic teaching materials with improved student achievement of Arabic Departement of STAI At-Tahdzib Ngoro Jombang.